2005
DOI: 10.1001/jama.293.7.817
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent HIV-1 Viremia (Blips) and Drug Resistance in Patients Receiving HAART

Abstract: REATMENT OF HUMAN IMMUNOdeficiency virus type 1 (HIV-1) infection with highly active antiretroviral therapy (HAART) can suppress viremia to below the limit of detection of available clinical assays. 1-3 The current goal of antiretroviral therapy is suppression of viremia to below 50 copies/mL of HIV-1 RNA, the limit of detection of the most sensitive available clinical assay. 4,5 Suppression to this level is necessary to prevent drug resistance, the major cause of treatment failure. 6,7 After achieving suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
321
1
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(362 citation statements)
references
References 53 publications
32
321
1
6
Order By: Relevance
“…The causation and significance of VL in the range >50 to <1000 copies/ml are debated 9 and the concept of 'blips' (transient low-level viremia without clinical consequences) complicates the picture. 11,12 Similar numbers of blips could plausibly be expected to occur at the time of the first, second and third VL, but among our patients 23% had low detectable VL on their first test and only 6% developed detectable VL later. Opportunistic infections can result in transient increases in VL, 8,13 but at the time of VL testing, only two patients had ongoing opportunistic infections (CMV retinitis and extra-pulmonary TB).…”
Section: Discussionsupporting
confidence: 60%
“…The causation and significance of VL in the range >50 to <1000 copies/ml are debated 9 and the concept of 'blips' (transient low-level viremia without clinical consequences) complicates the picture. 11,12 Similar numbers of blips could plausibly be expected to occur at the time of the first, second and third VL, but among our patients 23% had low detectable VL on their first test and only 6% developed detectable VL later. Opportunistic infections can result in transient increases in VL, 8,13 but at the time of VL testing, only two patients had ongoing opportunistic infections (CMV retinitis and extra-pulmonary TB).…”
Section: Discussionsupporting
confidence: 60%
“…This suggests that in the 81% of patients with a detectable viral load but no apparent mutations, adherence was inadequate for some reason, leading to a real risk that these patients would develop drug resistance over time. Even if we assumed that viral loads of under 1000 copies/ml might be related to ''blips'' (transient viraemia that returns spontaneously to undetectable levels without apparent clinical consequences, 14,15 ) there were only five (33%) of 15 patients with viral load titres ≥1000 copies/ml who had clinical and/or immunological signs suggesting failure. This implies that routine clinical examinations, pill-count monitoring, immunological and other existing forms of adherence monitoring would still miss the great majority of patients having inadequate viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, some blips may be associated to biological variability and test variability (±0.5 log 10 ) (Bryan et al, 2011). Although some studies associate blips occurrences with a higher frequency of relapse (Greub et al, 2002), most studies have confirmed that blips do not result in increased risk of virologic or clinical failure (García-Gasco et al, 2008), (Nettles et al, 2005).…”
Section: Hiv Patientsmentioning
confidence: 99%